OPTIMIZATION OF THE LOGISTIC SUPPLY OF AGRICULTURAL PRODUCTS IN WAR CONDITIONS - Kuziak В.; Balyk У.; Hreshchak М. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article proves that the logistics of agricultural products in times of war face many difficulties and serious limitations due to increased risks and instability in international relations. The main purpose of writing the article is to conduct an analysis of Ukrainian export goods; to research and identify the main problems; to specify the optimal ways for supplying agricultural products in the conditions of war. The authors have named the main problems of supplying agricultural products and their consequences during the war. Among the main problems, the authors identify economic sanctions against military conflicts, which limit access for the products to the market. This significantly complicates the export of agricultural products. The war has caused destruction to agricultural infrastructure, production facilities, and equipment, which will result in crop failures and a decrease in production. In general, military actions pose serious risks to the quality and safety of agricultural products due to soil, water, and air pollution from explosions and other factors. The war has been proven to affect the country’s financial stability, exchange rate and access to financial resources for farmers, agribusiness and workers in this sector may be at risk. It is well established that power outages have the greatest impact on warehouse logistics and can cause a variety of problems for households, businesses and infrastructure as a whole. As a result of war, countries may lose access to certain consumer markets, which may lead to reduced exports and loss of competitiveness in international markets. To achieve the set goal of the research, the authors used scientific methods that revealed the essence and ensured the conceptual integrity of the research: system analysis is used to study the dynamics of exports; a comparative analysis of the results of addressing the problems of supplying agricultural products; the logical method was applied to study findings of the research and shape conclusions.